Globalization and business masculinities in South Korea: top managers in the industrial sector - Kwon, Jaok (Social Sciences, 2019)
Along with the growing globalization of business, discussion concerning the “transnational business masculinity” has gained importance in recent years. Previous research on the transnational masculinity has argued for the convergence of business masculinity in a global level. This results partly from the fact that previous studies have concentrated largely on the West. Focusing on the Korean transnational corporations, this paper contributes theoretically by suggesting that the configuration process of business masculinity is neither linear nor straightforward towards convergence. Based on semi-structured, in-depth interviews with top managers in the industrial sector in South Korea (hereafter Korea), this paper clarifies that the construction process of the business masculinity is plural, multi-faceted, and divergent despite the emergence of convergence in combination with socioeconomic and political factors in the local, national, and global level.